MicroRNA167-Directed Regulation of the Auxin Response Factors GmARF8a and GmARF8b Is Required for Soybean Nodulation and Lateral Root Development . Issue 3 (4th May 2015) - Wang, Youning; Li, Kexue; Chen, Liang; Zou, Yanmin; Liu, Haipei; Tian, Yinping; Li, Dongxiao; Wang, Rui; Zhao, Fang; Ferguson, Brett J.; Gresshoff, Peter M.; Li, Xia
Abstract : The microRNA miR167 contributes to the nodulation of soybean via auxin response factors. Abstract: Legume root nodules convert atmospheric nitrogen gas into ammonium through symbiosis with a prokaryotic microsymbiont broadly called rhizobia. Auxin signaling is required for determinant nodule development; however, the molecular mechanism of auxin-mediated nodule formation remains largely unknown. Here, we show in soybean ( Glycine max ) that the microRNA miR167 acts as a positive regulator of lateral root organs, namely nodules and lateral roots. miR167c expression was up-regulated in the vasculature, pericycle, and cortex of soybean roots following inoculation with Bradyrhizobium japonicum strain USDA110 (the microsymbiont). It was found to positively regulate nodule numbers directly by repressing the target genes GmARF8a and GmARF8b (homologous genes of Arabidopsis [ Arabidopsis thaliana ] AtARF8 that encode auxin response factors). Moreover, the expression of miR167 and its targets was up- and down-regulated by auxin, respectively. The miR167 -GmARF8 module also positively regulated nodulation efficiency under low microsymbiont density, a condition often associated with environmental stress. The regulatory role of miR167 on nodule initiation was dependent on the Nod factor receptor GmNFR1α, and it acts upstream of the nodulation-associated genes NODULE INCEPTION, NODULATION SIGNALING PATHWAY1, EARLY NODULIN40-1, NF-YA1 (previously known as HAEM ACTIVATOR PROTEIN2-1 ), and NF-YA2 . miR167 also promoted lateral root numbers. Collectively, our findings establish a key role for the miR167 -GmARF8 module in auxin-mediated nodule and lateral root formation in soybean.